2003
DOI: 10.1055/s-2003-44622
|View full text |Cite
|
Sign up to set email alerts
|

Brucella Diskitis Mimicking Herniation without Spondylitis; MRI Findings

Abstract: A case of isolated brucella disk infection mimicking fragmented disk herniation is presented. MRI studies were performed two times in 6 months, both of which did not show any signs of spondylitis. Since brucella infections are seen along with spondylitis, this case has attracted our attention. We focused on radiological findings in this pure brucella disk infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The intervertebral disc can be infected without spondylitis, which is named discitis. In addition to back pain, disc herniation and sciatica can be described by the patient with discitis[51,52], therefore, this disease should be considered in the differential diagnosis of those symptoms. It was observed that the simultaneous existence of spondylolysis and spondylolisthesis with brucellar discitis caused misdiagnosis[53].…”
Section: Osteoarticular Manifestationsmentioning
confidence: 99%
“…The intervertebral disc can be infected without spondylitis, which is named discitis. In addition to back pain, disc herniation and sciatica can be described by the patient with discitis[51,52], therefore, this disease should be considered in the differential diagnosis of those symptoms. It was observed that the simultaneous existence of spondylolysis and spondylolisthesis with brucellar discitis caused misdiagnosis[53].…”
Section: Osteoarticular Manifestationsmentioning
confidence: 99%
“…Diskitis in the absence of spondylitis secondary to brucellosis has been reported but is exceedingly rare. 11 The only clinical manifestation that we can attribute to brucellosis are his lymphadenopathy and splenomegaly. The laboratory abnormalities of anemia and mild CRP and ESR elevations are compatible with brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracolumbar spinal tuberculosis involving the vertebral body and more for osteolytic destruction, destruction of lesion or most often involving a vertebral destruction sequestrum see multiple irregularities in the kitchen, often involving the destruction of the vertebral pedicle rear, adjacent vertebral density generally reduced, local tissue reactions were; intervertebral disc damage, uneven density, there are "stars" like dead bone residue scattered in which the adjacent vertebral endplates irregular bone destruction or disappearance, most accompanied by paraspinal abscess formation, and calcification within the common abscess, abscess often exceed the length of the vertebral lesion formation flow injection abscess, abscess edge signal enhancement [24,25]; tuberculosis of the spine is the most reliable MRI features "jump lesion" and thin and smooth abscess wall and enhanced well-defined paraspinal abnormal signal (Figure 17) [26,27]. The Brucella spondylitis and more involved in the lower lumbar vertebral segments and 1 -2 [2,17], which is characterized by thick, irregular enhanced MRI abscess wall and ill-defined paraspinal abnormal signal, T1WI showed low signal, T2WI high signal to bone destruction evident when, T2WI high signal on fat suppression such as vertebrae, discs, accessories and intraspinal showed heterogeneous high signal (Figure 18) [2,3,[28][29][30][31].…”
Section: Manifestation Of Ct: Destructions Of the Interverbebral DImentioning
confidence: 99%